Desain Sistem Penjernihan Air Berbasis Tenaga Surya untuk Pengolahan Air Bersih - Imaniah Sriwijayasih; Aang Wahidin; Priyambodo Nur Ardi Nugroho; Dika Rahayu Widiana; Sumardiono; Boedi Herijono; Rikky Leonard; Septaviola Dini Utami; Masaril Fatahilah; Cindy Putri Maharani (Proklamasi 45 University, 2025)
A slow sand filter is a natural water filtration system that uses fine quartz-rich sand as a filter medium. The filtration process runs by gravity at a slow and even speed over the entire surface of the sand, involving physical, biochemical and biological processes simultaneously. To achieve the desired water quality, the filtration system was designed using 8